Evaluation of pharmacokinetics and relative bioavailability of pentoxifylline and its metabolite in beagle dogs following different formulations - Xu, Yuxiang; Qie, Hongxin; Zhao, Haopeng; Gong, Wenlin; Wang, Peiyuan; Gao, Xiaonan; Gao, Jinglin; Feng, Zhangying; Wang, Mingxia (Frontiers in Pharmacology, 2024)
A single-oral-dose, two-period cross-over study with a 5 days washout period under fed condition was conducted in 6 beagle dogs to explore the pharmacokinetic characteristics and relative bioavailability between sustained-release (SR) tablets and enteric-coated (EC) tablets of pentoxifylline (PTX) and its metabolite. The results showed that M5 exhibited the highest exposure level, while M1 demonstrated the lowest in both the SR and EC tablet groups. For PTX and M1, the T1/2 were 0.42 and 0.55 h, with the tmax of 1.83 and 1.83 h, respectively in the SR tablet group; In the EC tablet group, the T1/2 were 0.38 and 0.47 h; However, a significantly prolonged absorption process was noted, with tmax values of 5.06 and 5.78 h. In contrast, M5 exhibited distinct pharmacokinetic differences compared to PTX and M1. For the SR tablets group, T1/2 and tmax were recorded at 2.03 and 3.08 h, respectively. In the EC tablets group, T1/2 and tmax were 1.67 and 5.78 h, respectively. As regard the geometric least squares mean (LSM) of AUC and Cmax for SR tablets and EC tablets, the ratios of SR/EC of PTX, M1 and M5 were 67.62% (90% CI, 50.49-90.55%), 78.18% (90% CI, 54.15-112.88%) and 119.11% (90% CI, 99.62-142.41%) for AUC(0-t); The ratios were 67.62% (90% CI, 50.50-90.55%), 78.36% (90% CI, 54.48-112.72%), and 119.39%(90% CI, 100.03-142.50%) for AUC(0-∞) and 54.36% (90% CI, 36.63-80.67%), 58.80% (90% CI, 40.84-84.66%), 100.51% (90% CI, 89.50-112.88%) for Cmax respectively. The AUC ratio predictions of bioconversion results indicated that there was no significant difference in the bioconversion of M1 between the SR tablets and EC tablets, with a conversion rate 0.37 and 0.36, respectively. In contrast, the conversion rate of M5 demonstrated a significant difference (P < 0.05) between the SR tablets and EC tablets, with the ratio of 3.09 and 1.91, respectively. Furthermore, the EC tablets group demonstrated notable inter-individual differences and irregular drug absorption following meals. Consequently, the SR tablets appeared to provide a more stable and controllable therapeutic effect in beagle dogs.